Carbon debris and fiber cleaving: Effects on potassium‐titanyl‐phosphate laser energy and chorioallantoic membrane model vessel coagulation. (25th March 2019) - Tracy, Lauren F.; Kobler, James B.; Van Stan, Jarrad H.; Burns, James A.
Abstract : Objectives/Hypothesis: Photoangiolytic precision afforded by the 532‐nm potassium‐titanyl‐phosphate (KTP) laser relies on predictable energy delivery. Inadequate energy output can cause vessel rupture, and excessive energy can cause thermal damage. The quality of the cleaved surface and carbon deposits from ablated tissue are two factors that could negatively impact fiber performance. The effects of these on energy output and blood vessel coagulation were assessed using a chorioallantoic membrane (CAM) model. Study Design: Comparative analysis. Methods: Laser fibers with carbon debris, optimal fiber cleaving, and suboptimal cleaving were inspected at three times magnification, and the light dispersion pattern of each fiber was rated. The average energy output from consecutive pulses through each fiber configuration was recorded. The effect of these fiber conditions on clinical efficacy was estimated by measuring vessel coagulation versus rupture in the CAM model. Repeated measures analysis of variance compared results. Results: Carbon debris and suboptimal cleaving resulted in decreased energy output in comparison to optimal cleaving ([−Δ244 mJ, d = 4.31, P < .001] and [−Δ195 mJ, d = 6.04, P < .001]). Optimal cleaving resulted in immediate coagulation of vessels. Fibers with suboptimal cleaving and carbon debris had unpredictable outcomes, requiring multiple pulses for coagulation or causing vessel rupture. Conclusions: KTP laser fiber function is significantly affected by fiber tip condition. Carbon debris and suboptimal cleaving create significant attenuation of energy, which results in an unpredictable angiolytic effect, as demonstrated by increased vessel rupture in the CAM model. Optimal recleaving of KTP laser fibers restores prior energy output and predictable coagulation. Care should be taken to avoid carbon debris on laser‐fiber tips and to cleave fibers properly. Level of Evidence: NA Laryngoscope, 129:2244–2248, 2019